PEDAGOGICAL COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS AND IMPROVING LEARNING OUTCOMES FOR CHILDREN WITH SPECIAL NEEDS - Muttaqin, Ahmad Ihwanul; Safira, Nurilia; Lubis, Ahmad Hafidz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article highlights the critical role of teacher competence, particularly pedagogical competence, in educating children with special needs to help them optimize their potential. Pedagogical competence enables teachers to effectively manage and develop the learning process, thereby enhancing learning outcomes. However, in practice, many Islamic Religious Education teachers fall short of these competency standards, which adversely affects the learning outcomes of students with special needs. This study is based on field research employing qualitative methods at the Junior High School for Children with Special Needs (SMPLB) in Lumajang. The findings indicate that improving learning outcomes requires active collaboration between teachers and students, particularly students with special needs, and demands teachers who possess strong pedagogical competence.